Influence of Education and Training (Training) The Motivation Administration and Employee Performance In Office of the President of Timor-Leste - Angelina da Luz Mota, Rita (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
This study aims to examine and analyze the influence of education and training on the motivation                                     and performance employees of Administration Office at the President of Timor-Leste based on survey approach. Type of this research were conducted at the President’s Office of  Timor-Leste.With the population in this study were permanent employees who work at the Administration Office of the President who has attended Training. Withdrawal procedure sample in this study uses total sampling the entire population is used as a sample study (saturated sample) because of small populations. Then the samples used in this study can be                                  defined as many as 66 people Employees. The results showed that: (1) education and training are positively and significant effect on motivation.            (2) education and training  are positively and significant directly effect on performance employees                               (3) education and training are positively effect on performance. Beside on the result of the research suggested to increase the performance of the employees  needs to conduct an assessment of the implementation of education and training of employees in  accordance with the need of the employees
Keywords: Education and Training, Motivation and Performance